Myeloid Derived Suppressor Cells Expansion Persists After Early ART and May Affect CD4 T Cell Recovery - Agrati, Chiara; Tumino, Nicola; Bordoni, Veronica; Pinnetti, Carmela; Sabatini, Andrea; Amendola, Alessandra; Abbate, Isabella; Lorenzini, Patrizia; Mondi, Annalisa; Casetti, Rita; Cimini, Eleonora; Grassi, Germana; et al. (Frontiers in Immunology, 2019)
Myeloid Derived Suppressor Cells (MDSC) are expanded during HIV-1 infection and correlated with disease progression. MDSC expand in the early phase of primary infection depending on TRAIL level. In this study we evaluated the effect of ART on the frequency of MDSC in patients with primary HIV infection (PHI), and their impact on CD4 T cell reconstitution. MDSC frequency was evaluated by flow-cytometry in 60 PHI patients at 12, 24 and 48 weeks after ART initiation. Cytokine plasma levels were evaluated by Luminex technology at the same time points. The capacity of MDSC to modulate hematopoietic early progenitor cells expansion was evaluated using the OP9/Dl1 in vitro system. As previously described, polymorphonuclear-MDSC (PMN-MDSC) frequency was higher in PHI compared to healthy donors. Interestingly, forty-eight weeks of successfully ART failed to normalize the PMN-MDSC frequency. Moreover, PMN-MDSC frequency was not correlated with residual viral load, suggesting that the persistence of PMN-MDSC was not due to residual viral replication. Interestingly, patients with low PMN-MDSC frequency (<6%) at T0 had a higher HIV DNA at the same time point than individuals with high PMN-MDSC group (>6%). We also found an inverse correlation between PMN-MDSC frequency and CD4-T cell count at 48 weeks post ART, which was confirmed by multivariate analysis adjusting for age and CD4 T cell number at baseline. This data suggest that the persistence of PMN-MDSC may impact CD4 T cell recovery. Indeed, in vitro PMN-MDSC impaired the expansion of CD34+CD38- hematopoietic early progenitors. Further, a balance between TRAIL and GM-CSF may be necessary to maintain a low MDSC level. In conclusion, early ART initiation was not able to normalize PMN-MDSC frequency that might impact the CD4 T cell recovery. These data open new question on the clinical impact of the MDSC persistence in HIV+ patients, in particular on the non-AIDS related diseases.